ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL CERITA PADA MATERI ARITMATIKA SOSIAL - Maria Indriyani, Lola; Minarti, Eva Dwi (IKIP Siliwangi, 2021)
This study aims to explain the mistakes of junior high school students in solving social arithmetic story problems and analyze the factors. The research method taken is descriptive qualitative. The research subjects were seventh grade students of SMP Negeri 8 Cimahi. Data collection in this study was carried out by using a mathematical test method with four questions of social arithmetic and interviews with students who made mistakes. The data analyzed were taken from 10 students' answers by means of data analysis used for this study, namely data reduction, data presentation and conclusion drawing. After the tests and interviews were carried out, the results of the tests and interviews with student answers were analyzed and conclusions were drawn about what mistakes students often experienced in solving story questions on social arithmetic material. From the results of the study, it was shown that the students' mistakes in working on story problems on social arithmetic material were that students did not understand the problem because the social arithmetic material given was about story questions, errors in making mathematical models, namely: students made mistakes in operating the answers. on the questions, and errors in the process or steps of working on the questions, namely: writing down what is known and determining what is being asked. Therefore, the factors that often cause students to make mistakes are that there are still many students who do not understand the basic concepts, students are less thorough in understanding story questions, so students do not understand the concept of arithmetic operations well.